Bahasa dan Kesantunan - Arman, Lidya (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2015)
Politeness, traditionally is governed by the norms of society are internalized in the context of the culture and local wisdom. The concept of modesty in the traditional language that it was time to "read" back theoretically, enable the ideology refresher on how the language should be used, to be polite. Behave or speak well mannered and ethical is relative, depending on the social distance speaker and hearer. In addition, the meaning of modesty and decency also understood the same in general; meanwhile, those two things are different. The term refers to an arrangement polite grammatical speech-based awareness that every person is entitled to be served with respect, while polite it means awareness of social distance. If the norms in the local traditions instill modesty in speaking, may not occur sorting between politeness (deference) and courtesy (politeness). This paper will provide theoretical views concerning the particulars politeness, which can be used as a reference to re-reflect on the use of everyday language. Reflection to see the value of modesty in the use of everyday language was necessary, where the language not only as an instrument of communication, but also the arena of self-realization was polite and ethical.